2018
DOI: 10.1136/heartjnl-2018-313171
|View full text |Cite
|
Sign up to set email alerts
|

Community study to uncover the full spectrum of rheumatic heart disease in Uganda

Abstract: Our data reveal a high prevalence of undiagnosed RHD within an endemic community and fill a critical gap in RHD epidemiology in African adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…In a study from Uganda, the prevalence of rheumatic HD in adults >20 years of age was 2.34% (95% CI, 1.49%–3.49%). 103…”
Section: Valvular Diseasesmentioning
confidence: 99%
“…In a study from Uganda, the prevalence of rheumatic HD in adults >20 years of age was 2.34% (95% CI, 1.49%–3.49%). 103…”
Section: Valvular Diseasesmentioning
confidence: 99%
“…Through echocardiographic screening, prior studies have demonstrated high prevalence rates of RHD, 2.5%–3% in the general population in Uganda 5–7. A country-wide RHD registry was developed in Uganda in 2010 to improve the care and follow-up of children and adults with RHD 8.…”
Section: Introductionmentioning
confidence: 99%
“…The overall prevalence of RHD in children screened in this study was only 1%, which was lower than anticipated. Previous screening studies in this region have shown a prevalence of 2.5-3% (13,17,18). While this study was not designed to understand this difference, it is possible that multiple prior echo screening studies, which included RHD education in schools, health centers, and in the community, may have increased awareness and subsequently reduced community rates of new RHD through improved primary and secondary prevention.…”
Section: Discussionmentioning
confidence: 93%